PENGARUH PUPUK ORGANIK BERBASIS AZOLLA, FOSFAT ALAM, DAN ABU SEKAM PADI TERHADAP HASIL KACANG TANAH DI ALFISOL - Anandeya Satrio Sambodo; Sudadi Sudadi; Sumarno Sumarno (Universitas Sebelas Maret, 2014)
This research to determine the effect of azolla-based organic fertilizers, rock phosphate, and rice husk ash, and the best combination treatment to peanut yield on Alfisols. The experiment was conducted in April-November 2013 at the paddy fields of farmers in Sukosari village, Jumantono, Karanganyar District and in Laboratory of Soil Chemistry and Fertility and Soil Biology and Biotechnology Laboratory, Department of Soil Science, Faculty of Agriculture UNS for soil chemical and biological properties respectively. This experimental design used was Randomized Block Completely Design (RCBD) with 5 treatments and each repeated 5 times. Statistical analysis of the data using the F test at 5% level of confidence followed by DMRT if any signicant influence. The variabels observed were soil organic matter content, soil pH, total number of soil bacteria, plant height, number of root nodules, and seed weight. The results showed that there was significant differences among the treatments. The treatment of P1 (5 tons/ha azolla compost, 100 kg/ha phosphate rock and 75 kg/ha rice husk ash) provide the highest of soil organic matter content (4.31%) while P2 (5 tons/ha azolla compost, 50 kg/ha phosphate rock and 37.5 kg/ha rice husk ash) provide the highest dry seed yield (1011.09 kg/ha) which was 11.06 % higher than control treatment (910.38 kg/ha).